2017
DOI: 10.1111/cns.12781
|View full text |Cite
|
Sign up to set email alerts
|

Finasteride inhibited brain dopaminergic system and open‐field behaviors in adolescent male rats

Abstract: These results suggest that finasteride inhibits dopaminergic system and open-field behaviors in adolescent male rats by inhibiting the conversion of testosterone to dihydrotestosterone, and imply finasteride as a potential therapeutic option for neuropsychiatric disorders associated with hyperactivities of dopaminergic system and androgen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 54 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…the Cyp17a1 inhibitor abiraterone. Along with studies using systemic finasteride [5αR inhibitor ( 163 , 164 , 222 , 223 )], these results suggest that local androgen synthesis regulates DA signaling in the mesocorticolimbic system and DA-dependent behaviors. While these studies are informative, there still remains an important gap in our understanding of how neural androgen production specifically influences executive functioning.…”
Section: Androgens Regulate Executive Functionmentioning
confidence: 69%
“…the Cyp17a1 inhibitor abiraterone. Along with studies using systemic finasteride [5αR inhibitor ( 163 , 164 , 222 , 223 )], these results suggest that local androgen synthesis regulates DA signaling in the mesocorticolimbic system and DA-dependent behaviors. While these studies are informative, there still remains an important gap in our understanding of how neural androgen production specifically influences executive functioning.…”
Section: Androgens Regulate Executive Functionmentioning
confidence: 69%
“…Immobility in TST may assess the strength and energy of the movement of mice, a sign of reluctance to maintain effort [ 66 , 67 ], while as previously reported, activity in OFT can reflect neurotransmitter system effects on stimulus salience and behavioral activity [ 68 , 69 ], suggesting a key role of ENZ on motivation to explore. Interestingly, pharmacological inhibition of T conversion to DHT in non-castrated adolescent rats affected exploratory and motor behaviors in OFT by down-regulating dopaminergic activity in SNpc and VTA [ 70 ]. These behavioral observations were strengthened by the expression of androgen components [ 50 ] within the nigrostriatal circuitry in TH+-structures.…”
Section: Discussionmentioning
confidence: 99%
“…58 Preclinical studies have demonstrated that treating rodents with finasteride increases depressive and anxiety phenotypes. 59,60 Despite the patient outcry, 58 accumulating evidence (for review, see Alhetheli et al, 50 Hirshburg et al, 51 and Traish 52 ), and high potential cost to benefit of the use of these compounds, there remain skeptics and advocates for their continued use 61 when in fact this is a significant issue for patients and a "surmountable challenge for clinicians". 52 Consistent with these clinical findings, preclinical studies demonstrate that finasteride treatment alters valence processing.…”
Section: Endogenous Neurosteroids and Affective Tonementioning
confidence: 99%